2019
DOI: 10.1055/s-0038-1677002
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Site Infection: The Clinical and Economic Impact

Abstract: Surgical site infection (SSI) following colorectal surgery is associated with worse postoperative outcomes, longer length of stay, and higher rates of readmission. SSI rates have been established as a surrogate metric for the overall quality of surgical care and are intricately tied to financial incentives and the public reputation of an institution. While risk factors and prevention mechanisms for SSI are well established, the rates of SSI remain high. This article discusses the clinical and economic impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 61 publications
2
23
0
Order By: Relevance
“…Prior studies implementing Colon Bundles have shown a significant reduction in superficial SSI rates from 57 to 70 %, but mixed effects on deep SSI rates [ 4 , 5 ]. Though some studies show a 70 % reduction in deep SSI rates [ 9 ], others show no effect [ 4 ]. Our Colon Bundle implementation shows that meaningful reduction in deep organ space infections is achievable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies implementing Colon Bundles have shown a significant reduction in superficial SSI rates from 57 to 70 %, but mixed effects on deep SSI rates [ 4 , 5 ]. Though some studies show a 70 % reduction in deep SSI rates [ 9 ], others show no effect [ 4 ]. Our Colon Bundle implementation shows that meaningful reduction in deep organ space infections is achievable.…”
Section: Discussionmentioning
confidence: 99%
“…Not only do SSIs prolong hospital length of stay and hospital costs [ 3 ], but they are also associated with an increased risk of death [ 1 ]. It has been shown that implementing colon bundles effectively reduce SSIs, however, such bundles are still not universally employed and there are varying elements included in the different bundles [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aside from the aforementioned adverse effects on clinical outcome, high infectious complication is linked with significant negative economic consequences. In fact, it is estimated that the USA spends more than $3 billion annually on SSIs [15]. Following the evidence related to immunonutrition with lower infectious complications, several studies have evaluated the cost-effectiveness of immunonutrition, comparing the cost and clinical effect versus conventional treatment (nonimmunonutrition).…”
Section: Evidence In Favor Of Preoperative Immunonutritionmentioning
confidence: 99%
“…In fact, colorectal surgery patients are disproportionately affected by SSI, with rates of up to 25%. Naturally, this is related to the clean-contaminated nature of many colorectal procedures, as well as exteriorization of the bowel; however, up to 55% of these infections have been deemed preventable [15].…”
mentioning
confidence: 99%
“…SSIs have a significant impact, not only on morbidity and mortality but also on a patient's experience of recovery following an operation [6]. SSIs present a significant financial burden both to the healthcare system, through extra inpatient bed days and the costs of additional primary and secondary care services, and to the patient, in terms of lost work days and travel to appointments, with a resultant economic impact for wider society [2,7].…”
Section: Introductionmentioning
confidence: 99%